Cannabinoid receptor 2 plays a pro-tumorigenic role in non-small cell lung cancer by limiting anti-tumor activity of CD8+ T and NK cells - Sarsembayeva, Arailym; Kienzl, Melanie; Gruden, Eva; Ristic, Dusica; Maitz, Kathrin; Valadez-Cosmes, Paulina; Santiso, Ana; Hasenoehrl, Carina; Brcic, Luka; Lindenmann, Jörg; Kargl, Julia; Schicho, Rudolf (Frontiers in Immunology, 2023)
Cannabinoid (CB) receptors (CB1 and CB2) are expressed on cancer cells and their expression influences carcinogenesis in various tumor entities. Cells of the tumor microenvironment (TME) also express CB receptors, however, their role in tumor development is still unclear. We, therefore, investigated the role of TME-derived CB1 and CB2 receptors in a model of non-small cell lung cancer (NSCLC). Leukocytes in the TME of mouse and human NSCLC express CB receptors, with CB2 showing higher expression than CB1. In the tumor model, using CB1- (CB1-/-) and CB2-knockout (CB2-/-) mice, only deficiency of CB2, but not of CB1, resulted in reduction of tumor burden vs. wild type (WT) littermates. This was accompanied by increased accumulation and tumoricidal activity of CD8+ T and natural killer cells, as well as increased expression of programmed death-1 (PD-1) and its ligand on lymphoid and myeloid cells, respectively. CB2-/- mice responded significantly better to anti-PD-1 therapy than WT mice. The treatment further increased infiltration of cytotoxic lymphocytes into the TME of CB2-/- mice. Our findings demonstrate that TME-derived CB2 dictates the immune cell recruitment into tumors and the responsiveness to anti-PD-1 therapy in a model of NSCLC. CB2 could serve as an adjuvant target for immunotherapy.